2020
DOI: 10.1016/j.csbj.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and challenges in protein stability prediction upon genome variations: towards future applications in precision medicine

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 88 publications
(114 reference statements)
1
119
0
Order By: Relevance
“…In the vast majority of cases, the folding-free energy of the mutants was found to be less favorable than of a wild type, and, thus, the dataset is biased toward de-stabilizing mutations. Series of works [ 26 , 43 , 44 , 45 ] were devoted on this topic and suggested that the training (and testing) dataset should have a similar number of cases of stabilizing and de-stabilizing mutations. While this is understandable from the point-of-view of statistics, we argue that this should not be necessarily applied in developing machine learning predictors of protein stability changes caused by mutations (especially for predictors that use only sequence information as SAAFEC-SEQ).…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of cases, the folding-free energy of the mutants was found to be less favorable than of a wild type, and, thus, the dataset is biased toward de-stabilizing mutations. Series of works [ 26 , 43 , 44 , 45 ] were devoted on this topic and suggested that the training (and testing) dataset should have a similar number of cases of stabilizing and de-stabilizing mutations. While this is understandable from the point-of-view of statistics, we argue that this should not be necessarily applied in developing machine learning predictors of protein stability changes caused by mutations (especially for predictors that use only sequence information as SAAFEC-SEQ).…”
Section: Discussionmentioning
confidence: 99%
“…Computational tools accounting for anti-symmetric properties of variation i.e. ΔΔG (A->B) = - ΔΔG (B->A) [118] , [141] , [142] are able to achieve improved prediction performance complementing experimental studies [85] .…”
Section: Discussionmentioning
confidence: 99%
“…It is not meant to be an exhaustive list, with other tools available centred on important questions like assessing cancer variations and other human mutations. As such, these go beyond the scope of this review and have been extensively reviewed elsewhere [83] , [84] , [85] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gerasimavicius et al have highlighted an improvement in the identification of pathogenic variations using |ΔΔG| values ( Gerasimavicius et al, 2020 ). However, very little is known about thermodynamic changes in human protein variants so far ( Sanavia et al, 2020 ), and the processes establishing whether a variation perturbing the protein stability is or not disease-related are not clear yet. An extensive comparative analysis has proven that, on average, variations mostly involved in disease also associated with large effects on protein stability ( Casadio et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%